An optical method to measure heart rate on human skin - Olmos Pena, J.; Abrego, N. P. Castellanos; Hernandez Pozos, J. L. (Pan American Health Care Exchanges (Online), 2017)
The aim of this work is to obtain measurements of heart rate in a noncontact way throughout the light reflected by the human skin with a portable instrument. The system was designed to apply a laser and to receive the reflected light from the skin where a vein is beating, later amplify and acquire the signal in a computer, processing and computing the frequency spectrum of the signal to obtain the heart rate. Other instruments have been developed with lasers beam but they suffer from portability, size and costs. Experiments were carried out with known signals: sinusoidal, triangle and square, 10 different frequencies ranging from 0.5 Hz to 4 Hz. Also the system was applied to humans where the heart rate was obtained. Results have shown confidence in heart rate measurements where, for known signals, a 5% of error was founded. For humans, 10 female and 10 male subjects, their heart rate was measured in the wrist using a very reflective membrane attached to the skin. Again the error was less than 5% and it decreased with an increase of heart rate. We have developed an instrument that could be used with confidence for the measurement of heart rate.